152k views
1 vote
I need help from uh all..​

I need help from uh all..​-example-1

1 Answer

4 votes

Answer:

Explanation:

Given expression is,


\text{cot}A=(1)/(2)(\text{cot}(A)/(2)-\text{tan}(A)/(2))

To prove this identity we will take the right side of the identity,


(1)/(2)(\text{cot}(A)/(2)-\text{tan}(A)/(2))=(1)/(2)(\frac{1}{\text{tan}(A)/(2)}-tan(A)/(2))


=(1)/(2)(\frac{1-\text{tan}^2(A)/(2)}{tan(A)/(2)})


=(1)/(2)[\frac{2(1-\text{tan}^2(A)/(2))}{2tan(A)/(2)}]


=(1)/(2)(\frac{2}{\text{tan}A} ) [Since
\text{tan}A=\frac{2\text{tan}(A)/(2)}{1-\text{tan}^2(A)/(2)}]

= cot A

Hence right side of the equation is equal to the left side of the equation.

User Williamg
by
4.5k points